FROM NARCISSISM TO AUTISM: A DIGIMODERNIST VERSION OF POST-POSTMODERN - Zahurska, Nataliia V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
In this article the causes and features of a shift from neurosis to narcissism and then autism were investigated. Moreover, special attention is paid not so much to the psychological or even psychiatric aspects of the problem, but to changes in the general features of a human being. Thus, when speaking of the transition from narcissism to autism, one is focusing on true autism, which is characterized by veracity, sincerity and authencity, which reveal themselves in the form of a special kind of infantility, a kind of mature infantility. A suitable example of such infantility is found in the animated film Shrek, a certain barbarism of which is not so ironic or even knowing ironic, but to a greater extent it is warm, earnest and serious although childish. Among other infantile practices, it is worth noting the situationalist-lettrist practice of organizing a text in the form of an ABC alphabet book, a hornbook, which is actualized in a digimodern context. True autism and to some extent pseudoautism in a certain sense become a way to cope with the trance and amnesia of pseudomodernism and leave a hope for the future. Thus, paradoxically, wholeness that was lost is restored through desocialization and sociopathy. This article also draws parallels between digimodernism and speculative realism, conceptualization of interpassivity as well as automodernity. It is emphasized that personal autonomy and automation can be achieved through the use of devices as a means of achieving productive loneliness, which should be distinguished from alienation. In this case, the widespread use of sensory experience as a way of communication is especially important, as an example of which Hope Sandoval’s mode of being and work are considered. It suggests that the high-tech / high-touch approach is best released in DIY activities. The above considerations allow to conclude that true autism is one of the most actual post-postmodern modes of subjectivation.